A Canadian qualitative study exploring the diversity of the experience of family caregivers of older adults with multiple chronic conditions using a social location perspective. Issue 1 (December 2016) - Williams, Allison; Sethi, Bharati; Duggleby, Wendy; Ploeg, Jenny; Markle-Reid, Maureen; Peacock, Shelley; Ghosh, Sunita
Abstract Background A little-studied issue in the provision of care at home by informal caregivers is the increase in older adult patients with chronic illness, and more specifically, multiple chronic conditions (MCC). We know little about the caregiving experience for this population, particularly as it is affected by social location, which refers to either a group's or individual's place/location in society at a given time, based on their intersecting demographics (age, gender, education, race, immigration status, geography, etc.). We have yet to fully comprehend the combined influence of these intersecting axes on caregivers' health and wellbeing, and attempt to do this by using an intersectionality approach in answering the following research question:How does social location influence the experience of family caregivers of older adults with MCC? Methods The data presented herein is a thematic analysis of a qualitative sub-set of a large two-province study conducted using a repeated-measures embedded mixed method design. A survey sub-set of 20 survey participants per province (n = 40 total) were invited to participate in a semi-structured interview. In the first stage of data analysis, Charmaz's (2006) Constructivist Grounded Theory Method (CGTM) was used to develop initial codes, focused codes, categories and descriptive themes. In the second and the third stages of analysis, intersectionality was used to develop final analytical themes. Results The following four themes describe the overall study findings: (1) Caregiving Trajectory, where three caregiving phases were identified; (2) Work, Family, and Caregiving, where the impact of caregiving was discussed on other areas of caregivers' lives; (3) Personal and Structural Determinants of Caregiving, where caregiving sustainability and coping were deliberated, and; (4) Finding Meaning/Self in Caregiving, where meaning-making was highlighted. Conclusions The intersectionality approach presented a number of axes of diversity as comparatively more important than others; these included gender, age, education, employment status, ethnicity, and degree of social connectedness. This can inform caregiver policy and programs to sustain health and well-being.